ANALYSIS OF THE FORMATION OF TOXIC LANGUAGE OF MOBILE LEGEND ONLINE GAME STREAMERS ON THE YOUTUBE CHANNEL “TOP GLOBAL MIYA” (MORPHOLOGICAL STUDY) - romadhona, Ahlan; Afif Ardiansyah, Muhammad; Sancity, Nixie; Dwi Rohmah, Laili; Lulua, Lisa; Afkar, Taswirul (Universitas Islam Zainul Hasan Genggong, 2025)
This research discusses the analysis of the formation of toxic language, morphological studies used by streamers of the online game Mobile Legend. This research aims to analyze the formation of toxic language which is often used when streamers play games on Bang Pascol's Top Global Miya YouTube channel. This research uses descriptive and analytical methods in the pronunciation of toxic language in YouTube content to obtain data. The results showed that toxic words, such as